HUBUNGAN ANTARA PERSEPSI TERHADAP KETERLIBATAN AYAH DALAM PENGASUHAN DENGAN KONSEP DIRI PADA SISWA KELAS X SMK NEGERI 4 KENDARI - Marsuq, Alfira faradila; Kristiana, Ika Febrian (Empati, 2017)
This study aims to determine the relationship between perceptions of father's involvement in parenting with self-concept in students of class X SMK Negeri 4 Kendari. The hypothesis of the proposed research is there is a positive relationship between perceptions of father's involvement in parenting with self-concept in the students of class X SMK Negeri 4 Kendari. The population in this study are students of class X SMK Negeri 4 Kendari as many as 284 students with 157 students of research sample. This research uses cluster random sampling technique. Methods of data collection using psychological scale, namely the scale of perception of father's involvement in parenting and the scale of self-concept. The perception scale of father involvement in nurturing consists of 39 valid aitems (Î± = 0.925) and self-concept scales consisting of 23 valid items (Î± = 0.834) that have been tested on 114 students. Data analysis was done by simple regression analysis method. The result of data analysis show correlation coefficient (rxy) = 0,476 at P = 0,000 (p <0,05). This means that the hypothesis of this research is accepted that there is a positive relationship between perceptions of father's involvement in parenting with self-concept. Effective contribution of the perception of father's involvement in self-care is 22.7% while 77.3% comes from other factors not revealed in this research.Â